2003
DOI: 10.1086/375059
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Artesunate and Quinine in the Treatment of Severe Falciparum Malaria

Abstract: A randomized, open-label comparison of artesunate and quinine was conducted in 113 adults with clinically severe falciparum malaria in western Thailand. Mortality was 12% with artesunate and 22% with quinine treatment (relative risk, 0.53; 95% confidence interval, 0.23-1.26; P=.22). Multiple logistic regression analysis found admission plasma lactate level, Glasgow Coma Scale score, and total serum bilirubin level to be independent risk factors for death. Coma recovery and times to normalize plasma lactate lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
62
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 42 publications
2
62
1
2
Order By: Relevance
“…Likewise, it has been observed previously that fever clearance time and parasite clearance time (16.0 and 22.4 hours, respectively) were shorter when intramuscular artemether was compared with quinine in the treatment of Sudanese children with severe P. falciparum malaria in eastern Sudan [10]. The mean parasite clearance time shown in this study was relatively shorter than the results (68 hours) obtained from other studies in Southeast Asia [14] and a parasite clearance time of 29.5 hours that was reported among non-immunized European travelers [15]. Interestingly, while Praygod et al, in their review of twelve trials (1,524 patients), found no significant difference in parasite clearance time or fever clearance time between one parenteral artemisinin derivative (artemether, β-arteether/artemotil, or artesunate) and quinine [16]; however, Sinalr et al observed the superiority of parenteral artesunate over quinine for the treatment of severe malaria in both adults and children and in different regions of the world in their recent review.…”
Section: Discussionsupporting
confidence: 55%
“…Likewise, it has been observed previously that fever clearance time and parasite clearance time (16.0 and 22.4 hours, respectively) were shorter when intramuscular artemether was compared with quinine in the treatment of Sudanese children with severe P. falciparum malaria in eastern Sudan [10]. The mean parasite clearance time shown in this study was relatively shorter than the results (68 hours) obtained from other studies in Southeast Asia [14] and a parasite clearance time of 29.5 hours that was reported among non-immunized European travelers [15]. Interestingly, while Praygod et al, in their review of twelve trials (1,524 patients), found no significant difference in parasite clearance time or fever clearance time between one parenteral artemisinin derivative (artemether, β-arteether/artemotil, or artesunate) and quinine [16]; however, Sinalr et al observed the superiority of parenteral artesunate over quinine for the treatment of severe malaria in both adults and children and in different regions of the world in their recent review.…”
Section: Discussionsupporting
confidence: 55%
“…Patients aged 16 to 65 years were included if they or an attending relative were able and willing to give informed written consent and if they had slide-confirmed, single species P. falciparum parasitemia; no contraindications to doxycycline; a negative pregnancy test for females of reproductive age; no requirement for interacting drugs (warfarin, bismuth, antacids, aluminum, magnesium, calcium, iron, zinc salts, or sucralfate); and clinically severe malaria (14,29). Ethical clearance was granted by the Ministry of Public Health, Government of Thailand.…”
mentioning
confidence: 99%
“…Axillary temperature, hematocrit, and parasite counts were measured every 6 h until parasite clearance (14). When the patient was able to eat, doxycycline was started.…”
mentioning
confidence: 99%
“…Artemether is used orally in combination with lumefantrine or mefloquine in the treatment of uncomplicated falciparum malaria or is given by intramuscular injection in severely ill patients. Intravenous or intramuscular artesunate, a water-soluble artemisinin derivative, and intramuscular artemether are increasingly used for the treatment of patients with malaria and vomiting or patients with severe malaria (2,4,5,9,11). Unlike artesunate, there is no intravenous preparation of artemether, as artemether is insoluble in water and must be dissolved in oils.…”
mentioning
confidence: 99%